Production And Characterization Of Biosurfactant Produced By Mangrove Streptomyces Sp. Pbd-410l - Rusly, Norazurin Syuhada (2019)
Biosurfactants are microbially produced surface-active compounds that reduce the surface tension between liquid phases of differing polarity. Presently, the best reported biosurfactant producers are Pseudomonas and Bacillus spp. Unfortunately, they are known opportunistic human pathogens, with some having antibiotic-resistance, causing grave concerns. Filamentous actinobacteria can be safer alternative biosurfactant producers, with no known human pathogenicity. The present study focused on the identification of biosurfactant-producing actinobacterium, characterization of the biosurfactant produced and the effect of fermentation parameters on biosurfactant production. A total of 60 actinobacterial isolates from mangrove sediments were screened for biosurfactant production using palm oil as the main carbon source. The presence of biosurfactant was confirmed using surface tension (ST) measurement, oil spreading technique (OST) and emulsification index (E24). Isolate PBD-410L was selected as the best biosurfactant producer based on the highest value for OST (68.0±1.7 mm) and the lowest surface tension measurement (39.7±0.6 dynes/cm). This isolate was characterized and tentatively identified as Streptomyces sp. PBD-410L, based on morphological characteristics and molecular identification. Crude biosurfactant extract was successfully recovered at a concentration of 11.04 g/L by using chloroform/methanol (2:1 v/v) mixture. The percentage yield on palm oil was 40.8%, giving 70.7 mm diameter in oil spreading technique.